PENGARUH PENERAPAN OUTDOOR MODELLING MATHEMATICS BERDIFERENSIASI PADA PEMBELAJARAN MATERI STATISTIKA TERHADAP KEMAMPUAN LITERASI MATEMATIS SISWA KELAS VIII SMP NEGERI 5 PELEPAT ILIR - Dewi Iriani; Sofnidar Sofnidar; Evandre Crisson Kholiq (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2026)
This study was motivated by the low mathematical literacy skills of students in class VIII SMP Negeri 5 Pelepat Ilir. This study aims to determine the effect of the application of mathematics learning outdoor mathematic education model on students' mathematical literacy skills. This research focused on statistics material in class VIII SMP Negeri 5 Pelepat Ilir. The research method used is quantitative research method with experimental type. The experimental design used is a quasi experiment design in the form of postest only control design, the classes used for research are 2 classes, namely the experimental class and the control class. The sampling technique used cluster random sampling. Hypothesis testing using independent sample t test and cohen's d effect size assisted by SPSS software. The results of the independent sample t test obtained a significance value of 0.029, this shows sig (2-tailed) <0.05, then ????0 is rejected and ????1 is accepted. While the results of the cohen's d effect size test obtained amounted to 0.560 which is included in the moderate effect category. It can be concluded that there is a significant effect of the application of the outdoor mathematics learning model on the mathematical literacy skills of VIII grade students of SMP Negeri 5 Pelepat Ilir